Displaying emergency patient estimated wait times: A multi‐centre, qualitative study of patient, community, paramedic and health administrator perspectives. (28th September 2020) - Walker, Katie; Stephenson, Melanie; Loupis, Anne; Ben‐Meir, Michael; Joe, Keith; Stephenson, Michael; Lowthian, Judy; Yip, Beatrice; Wu, Elena; Hansen, Kim; Rosler, Rachel; Buntine, Paul; et al.
Abstract: Objective: EDs have the potential ability to predict patient wait times and to display this to patients and other stakeholders. Little is known about whether consumers and stakeholders would want this information and how wait time predictions might be used. The aim of the present study was to gain perspectives from consumers and health services personnel regarding the concept of emergency wait time visibility. Methods: We conducted a qualitative interview and focus group study in 2019. Participants included emergency medicine patients, families, paramedics, well community members, and hospital/paramedic administrators from multiple EDs and organisations in Victoria, Australia. Transcripts were coded and themes presented. Results: One focus group and 103 semi‐structured interviews were conducted in 2019 including 32 patients, 22 carers/advocates and 21 paramedics in the ED; 20 health service administrators (paramedic and hospital) and 15 community members. Consumers and paramedics face physical and psychological difficulties when wait times are not visible. Consumers believe about a 2‐h wait is tolerable, beyond this most begin to consider alternative strategies for seeking care. Consumers want to see triage to doctor times; paramedics want door‐to‐off stretcher times (for all possible transport destinations); with 47 of 50 consumers and 30 of 31 paramedics potentially using this information. About 28 of 50 consumers would use times to inform facility or provider choice, another 19 of 50 want information once in the waiting room. During prolonged waits, 51 of 52 consumers would continue to seek care. Conclusions: Consumers and paramedics want wait time information visibility. They would use the information in a variety of ways, both pre‐hospital and while waiting for care. Abstract : This large qualitative, multi‐centre study interviewed patients, families, paramedics and other emergency stakeholders about emergency wait time displays. Consumers and paramedics want wait time information visibility. They would use the information in a variety of ways, both pre‐hospital and whilst waiting for care.